Digital Panopticon and Shattered Self: Unveiling AI Surveillance in Dave Eggers’s The Circle - Khan, Noman Hassan (Pakistan Languages and Humanities Review, 2024)
The paper aims to discuss the emergence of AI surveillance in contemporary dystopian fiction, which presents the reimagined digital panopticon disintegrating human identities and resulting in a shattered self, as portrayed in Eggers’ The Circle. Artificial Intelligence refers to the imitation of human intelligence by machinery, especially in making decisions, pattern recognition, and technological surveillance. The Circle depicts this through Mae Holland, whose integration into the tech company that values transparency above privacy causes the disintegration of an authentic self. Using the qualitative method, the study employs the concept of a digital panopticon to examine how AI-powered surveillance influences the protagonist. The findings reveal that Mae succumbs to self-regulation, leading to identity fragmentation, highlighting the psychological and social consequences of AI surveillance and its threat to individuality. It recommends the ethical advancements in technology, along with check and balance of tech companies, and priority of real human connections to protect individuality and privacy.